The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.52970/grmapb.v1i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Service Dominant Logic and Business Model Canvas: Narrative Study of Village Tourism

Abstract: The purpose of this research is to design service design, design a canvas business model (BMC) based on the design of services that have been designed and know the role of society. The required data is divided into two, namely primary data and secondary data. Primary data was obtained by conducting interviews and observations to tourists, managers and the community around Siregar Aek Nalas. Primary data obtained such as access, amenities, safety and security, processes, physical or digital artifacts, stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Conversely, if the expectations are not achieved, the quality of the service does not meet what it wants, or the company fails to serve its customers. If the expectations are the same as those obtained, the consumer is satisfied (Simanjuntak, 2021;Simanjuntak & Putra, 2021). Satisfaction is the level of one's feelings after comparing the perceived performance (results) with his expectations.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Conversely, if the expectations are not achieved, the quality of the service does not meet what it wants, or the company fails to serve its customers. If the expectations are the same as those obtained, the consumer is satisfied (Simanjuntak, 2021;Simanjuntak & Putra, 2021). Satisfaction is the level of one's feelings after comparing the perceived performance (results) with his expectations.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Penentuan pemasaran agar produk yang dimiliki oleh pelaku usaha dapat dikenal dan laku dipasar serta dapat diketahui oleh publik dibutuhkan strategi marketing yang jeli untuk menambah pundi keuntungan UMKM [12]. Pelaku usaha sejauh ini menerapkan strategi marketing menggunakan berbagai cara yaitu diantaranya menggunakan media sosial berupa instagram, group WA, dan facebook [13], [14]. Disatu sisi pada Instagram apabila tidak memiliki jumlah follower yang cukup tentunya berpengaruh pada penjualan karena yang melihat produk yang menjadi konten kurang diminati.…”
Section: ) Strategi Marketingunclassified
“…Utilising 347 migrant visitors in Ghana, Preko (2021) concluded that safety and security play a vital role in wealthy tourism development, which might contribute to the intention of the diaspora to recommend the destination as safe for tourists. Despite existing studies (Agarwal et al, 2021;Mawby et al, 2021;Simanjuntak, 2021), there is limited research in terms of the diasporic view of safety and security (Preko, 2021). This is, however, neglected within halal tourism from a non-Islamic country's perspective, utilising TPB, leading to the seventh hypothesis:…”
Section: Halal Safety and Security (Hsns)mentioning
confidence: 99%